Sensor Localization Using Fixed and Dynamic Communication Ranges in Different Types of Distributed Sensor Networks - SERAP KARAGOL; Dogan YILDIZ; Prabhat Ranjan PATHAK (International Journal of Applied Methods in Electronics and Computers, 2016)
Abstract: Wireless Sensor Network (WSN) refers to a group of locationally dispensed and dedicated sensors for observing and recording the physical conditions of the environment and coordinating the aggregated data at a centrical location. To serve such new applications, localization is largely used in WSNs to define the current location of the sensor nodes. Time of Arrival (ToA) localization is one of the prevalent schemes due to its high estimation accuracy. ToA is a method to estimate the location of a target based on the correlation of the signals and calculating the distances from each anchor to the target by multiplying the speed of light and the time at which the signal is received. In our recent study, we propose Modified 3N algorithm in 2D space. In the Modified 3N algorithm in 2D, three circles were used to localize the target nodes in the network. In this paper; Uniform, Beta, Weibull, Gamma and Generalized Pareto distributed networks are used for localization with the Modified 3N algorithm in 2D and the localization performance of the networks are evaluated and compared using MATLAB simulations. For these simulations, firstly, constant communication range of 10% of the field dimension is used and then dynamic communication ranges that depend on the number of total nodes are used for the same areas.